Pengaruh Penambahan Wollastonite dan Variasi GCC/PCC Terhadap Kekuatan Kertas Dalam Proses Pembuatan Kertas - Nurhayati, Nurhayati; Zulfansyah, Zulfansyah; Rionaldo, Hari; Hasudungan, Janso (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Filler is one of component used in papermaking industry to reduce production cost and improve paper properties. Ground Calcium Carbonate (GCC) and Precipitated Calcium Carbonate (PCC) are the most effective filler used in papermaking process. However, high usage of GCC and PCC may decrease paper strength. As an attempt to increase filler application in the papermaking process, wollastonite / calcium silicate is used as an additive to increase filler retention, without reduction in paper strength. The filler modification was done by adding 2% wollastonite per total filler dose. This study will evaluate the effect of adding wollastonite on filler retention and paper strength at filler doses of 21, 23 and 25% with variations in the percentage composition of PCC / GCC from 100/0, 90/10, and 80/20. The addition of wollastonite to filler with the resulted in increasing filler retention and no significant change in tensile index. Basis weight and thickness also showed stable values. The best filler retention obtained at 23% filler dose, with filler composition of 90% PCC 90% and 10% GCC, which resulted in 99% filler retention of the total filler dose added. The addition of 2% wollastonite in paper-making process will increase filler dose from 21% to 23%, which reducing fiber usage, therefore it the addition of wollastonite has the potential to reduce raw material costs by 5.8 USD / ton.Keyword : Filler, Filler retention, PCC, GCC, Wollastonite